Survival after in-hospital cardiac arrest is highly associated with the Age-combined Charlson Co-morbidity Index in a cohort study from a two-site Swedish University hospital. (February 2016) - Piscator, Eva; Hedberg, Pontus; Göransson, Katarina; Djärv, Therese
Abstract: Background: In-hospital cardiac arrest (IHCA) has a poor prognosis and clinicians often write "Do-Not-Attempt-Resuscitation" (DNAR) orders based on co-morbidities. Aim: To assess the impact of the Age-combined Charlson Co-morbidity Index (ACCI) on 30-days survival after IHCA. Material and methods: All patients suffering IHCA at Karolinska University Hospital between 1st January and 31st December 2014 were included. Data regarding patient characteristics, co-morbidities and survival were drawn from the electronic patient records. Co-morbidities were assessed prior to the IHCA as ICD-10 codes according to the ACCI. Differences in survival were assessed with adjusted logistic regression models and presented as Odds Ratios with 95% Confidence Intervals (OR, 95% CI) between patients with an ACCI of 0–4 points versus those with 5–7 points, as well as those with ≥8 points. Adjustments included hospital site, heart rhythm, ECG surveillance, witnessed status and place of IHCA. Results: In all, 174 patients suffered IHCA, of whom 41 (24%) survived at least 30 days. Patients with an ACCI of 5–7 points had a minor chance and those with an ACCI of ≥8 points had a minimal chance of surviving IHCA compared to those with an ACCI of 0–4 points (adjusted OR 0.10, 95% CI 0.04–0.26 and OR 0.04, 95% CI 0.03–0.42, respectively). Conclusion: Patients with a moderate or severe burden of ACCI have a minor chance of surviving an IHCA. This information could be used as part of the decision tools during ongoing CPR, and could be an aid for clinicians in planning care and discussing DNAR orders.